2017
DOI: 10.1177/2324709617734248
|View full text |Cite
|
Sign up to set email alerts
|

Pathologic Findings of Chronic PML-IRIS in a Patient with Prolonged PML Survival Following Natalizumab Treatment

Abstract: Immune reconstitution inflammatory syndrome (IRIS) is a common complication during treatment for natalizumab-associated progressive multifocal leukoencephalopathy (PML). Although severe IRIS can result in acute worsening of disability and is associated with poor prognosis, effective immune reconstitution may account for the high survival rate of this cohort of PML patients. We present pathological evidence of chronic IRIS 3.5 years after diagnosis with natalizumab-associated PML. Our case showed that the IRIS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 20 publications
(30 reference statements)
1
9
0
Order By: Relevance
“…In follow-up studies of people who survived PML, persistence of JCV in the CSF has been detected for as long as 3 years 65,188,189 . Similarly, post-mortem studies have revealed persistence of JCV DNA in the brains of longterm survivors of HIV-related PML and natalizumabrelated PML 66,190,191 . This evidence suggests that, despite immune reconstitution and clinical stabilization, JCV is not always cleared from the CNS but can instead return to a state of latency or persistent infection.…”
Section: Treatment Strategiesmentioning
confidence: 94%
See 1 more Smart Citation
“…In follow-up studies of people who survived PML, persistence of JCV in the CSF has been detected for as long as 3 years 65,188,189 . Similarly, post-mortem studies have revealed persistence of JCV DNA in the brains of longterm survivors of HIV-related PML and natalizumabrelated PML 66,190,191 . This evidence suggests that, despite immune reconstitution and clinical stabilization, JCV is not always cleared from the CNS but can instead return to a state of latency or persistent infection.…”
Section: Treatment Strategiesmentioning
confidence: 94%
“…Given that survival has increased with successful immune reconstitution, a fourth stage can be proposed, in which the host-virus equilibrium is re-established and, in some patients, persistent infection with a rearranged pathogenic virus ensues. Indeed, viral persistence with low copy detection in the CSF for years after clinical stabilization has been observed in some people who have survived PML 65,66 . The risk that PML will recur in these patients is unknown but is not negligible 67 ( fig.…”
Section: Pathogenesis Of Pmlmentioning
confidence: 99%
“…Thus, the definition of IRIS, “a paradoxical clinical deterioration, typically occurring in the face of immunologic recovery”, is a clinical concept for which the pathology and immunology have not fully been elucidated. In the post-mortem brain, fatal PML-IRIS is characterized by excessive CD8 + T-cell infiltration without CD4 + T-cells, even with the clearance of JCV antigen (5-7). In contrast, in biopsied cases, pathological examinations revealed T-cell infiltration with a well-balanced CD4/CD8 ratio in the presence of plasma cells (8).…”
Section: Introductionmentioning
confidence: 99%
“…Although case 9 did not have MRI visible lesions at the time with viremia and high CSF viral load, there could be diffuse pathological tissue-level changes as we showed in our previous case report. 74 JCV was also found on autopsy in immunocompetent individuals 75 without clinical evidence of PML.…”
Section: Discussionmentioning
confidence: 85%